2022
DOI: 10.3390/fluids7110344
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning Forecasts a Strained Turbulent Flow Velocity Field in Temporal Lagrangian Framework: Comparison of LSTM and GRU

Abstract: The subject of this study presents an employed method in deep learning to create a model and predict the following period of turbulent flow velocity. The applied data in this study are extracted datasets from simulated turbulent flow in the laboratory with the Taylor microscale Reynolds numbers in the range of 90 < Rλ< 110. The flow has been seeded with tracer particles. The turbulent intensity of the flow is created and controlled by eight impellers placed in a turbulence facility. The flow deformation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…It is reported that GRU is faster and produces similar prediction results as LSTM with fewer data [4,11,12,15]. In this study, 6,225,457 tracking points are available just from the 0.4 s long period of the experiment.…”
Section: Parallel Computing Assessmentmentioning
confidence: 94%
See 4 more Smart Citations
“…It is reported that GRU is faster and produces similar prediction results as LSTM with fewer data [4,11,12,15]. In this study, 6,225,457 tracking points are available just from the 0.4 s long period of the experiment.…”
Section: Parallel Computing Assessmentmentioning
confidence: 94%
“…This architecture establishes two significant features: the reset gate captures short-term dependencies and the update gate models' long-term dependencies in sequences [28]. is the hidden state from the previous step, X (t) is the current input, h (t) is a new hidden state, y (t) is the output, r (t) is the reset gate, z (t) is the update gate, g (t) is the candidate hidden state, σ is the sigmoid function, and tanh is the hyperbolic tangent function [15].…”
Section: Gated Recurrent Unit Modelmentioning
confidence: 99%
See 3 more Smart Citations